Properties of concrete containing finely crushed oil palm shell as partial sand replacement - Nurul Asyikin , Zulkepli (2012)
Oil palm shell is a waste which is abundantly generated and disposed at the landfill by Malaysian palm oil industry. As a result, it contributes toward pollution problem. Using OPS, as partial fine aggregate replacement in concrete making would be able to reduce the amount of this waste ending up at landfill. This thesis presents an experimental study on the workability, compressive strength and moisture absorption of concrete consisting finely crushed OPS as partial and fully fine aggregate replacement. Two types of mixes are prepared. One consists of a control mix and another one consist various percentages of finely crushed OPS. The influenced of finely crushed OPS with several replacements on the properties of concrete have been investigated. The workability and compressive strength decrease with an increase in the percentage of finely crushed OPS used. Moisture absorption of concrete increase as the amount of finely crushed OPS added becomes larger. The results revealed that mix consisting around 25% of finely crushed OPS is suitable for the application in the structural concrete material.